Estudo das interações de peptídeos antimicrobianos e sistemas miméticos de membrana por dinâmica molecular - Baldissera, Gisele [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Many peptides extracted from plants and animal secretions exhibit a broad spectrum of antimicrobial activity against bacteria gram-negative, gram-positive, fungi and parasites. Due this characteristic and the increasing resistance of pathogenic microorganisms to conventional forms of treatment, it is speculated the use of these peptides as potential new drugs. Therefore, various experimental and theoretical techniques that make use of membrane mimetic systems have been used to study the mechanisms of action of this class of peptides. In this work, we use molecular dynamics simulations to understand the influence of some characteristics of interaction peptide-peptide and peptide-membrane on biological efficiency of the Protonectins and Jelleines. Protonectin and Protonectin 1-6 are antimicrobial peptides, the first shows hemolytic activity, mast cell degranulation and chemotaxis, while the second presents chemotactic activity. Experimental data indicate that the association between those two peptides (1:1) generates a supramolecular aggregate structure and also increases the hemolytic and mast cell degranulation activities, while the chemotactic activity decreases, i.e., in combination they exhibit accentuated behavior of the interaction with membranes. Based on these results in this work, we speculate, which the interactions between Protonectin/Protonectin 1-6 (mixture) that would be associated with the formation of aggregate structure and the implications of this structure in the interaction with membrane mechanism. The results of the simulations in water and SDS micelle for these peptides indicate that there is a tendency of aggregation between pure Protonectins and Protonectin/Protonectin 1-6, and that this occurs through intermittent hydrogen bonds. Furthermore, it was found that the electrostatic interactions between the mixture of peptides is less favorable than for the pure Protonectins, influencing the distance between the ...

Muitos peptídeos extraídos de plantas e secreções de animais exibem um amplo espectro de atividade antimicrobiana contra bactérias gram-positivas, negativas, fungos e parasitas. Devido a essa característica e ao crescente aumento da resistência dos microrganismos patogênicos às formas de tratamento convencionais, especula-se a utilização destes peptídeos como possíveis novos fármacos. Por isso, várias técnicas experimentais e teóricas que fazem uso de sistemas miméticos do ambiente membranar têm sido utilizadas para se estudar os mecanismos de ação desta classe de peptídeos. No presente trabalho, utilizam-se simulações por Dinâmica Molecular com o intuito de investigar a influência de algumas características de interação peptídeo-peptídeo e peptídeo-membrana sobre a eficiência biológica de Protonectinas e Jeleínas. Protonectina e Protonectina 1-6 são peptídeos antimicrobianos, o primeiro apresenta atividade hemolítica, de degranulação de mastócitos e quimiotática, enquanto o segundo apresenta somente a atividade quimiotática. Dados experimentais indicam que a associação destes dois peptídeos (proporção 1:1) gera uma forma de estrutura supramolecular agregada e também aumenta as atividades hemolíticas e de degranulação de mastócitos, enquanto a atividade quimiotática decresce acentuadamente, ou seja, em associação eles apresentam um comportamento mais acentuado de interação com membranas. Tendo em vista estes resultados, especulam-se, neste trabalho, quais as interações entre Protonectina/Protonectina 1-6 (mistura) que estariam associadas à formação de tal estrutura agregada e quais as implicações desta estrutura no mecanismo de interação com membrana. Os resultados das simulações em água e micela de SDS para estes peptídeos indicam que há a tendência de agregação entre Protonectinas puras e Protonectina/Protonectina 1-6, e que esta ocorre por meio de ligações por ...
Keywords: Biologia molecular; Biofísica; Dinamica molecular; Peptídeos antibióticos; Membranas (Biologia); Biophysics